2016
DOI: 10.1017/thg.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

The Placenta in Twin-to-Twin Transfusion Syndrome and Twin Anemia Polycythemia Sequence

Abstract: Twin-to-twin transfusion syndrome (TTTS) and twin anemia polycythemia sequence (TAPS) are complications unique to monochorionic twin pregnancies and their shared circulation. Both are the result of the transfusion imbalance in the intertwin circulation. TTTS is characterized by an amniotic fluid discordance, whereas in TAPS, there is a severe discordance in hemoglobin levels. The article gives an overview of the typical features of TTTS and TAPS placentas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…FGR can be challenging to diagnose as placental function cannot currently be directly measured. Surrogate markers, such as abnormal fetal growth trajectory or abnormal blood flow to the placenta, are used with varying success. At present, there is no treatment for FGR, or the associated condition pre‐eclampsia; however, trials are exploring several new therapeutic avenues, including sildenafil, esomeprazole, metformin, pravastatin, and vascular endothelial growth factor maternal gene therapy .…”
Section: Introductionmentioning
confidence: 99%
“…FGR can be challenging to diagnose as placental function cannot currently be directly measured. Surrogate markers, such as abnormal fetal growth trajectory or abnormal blood flow to the placenta, are used with varying success. At present, there is no treatment for FGR, or the associated condition pre‐eclampsia; however, trials are exploring several new therapeutic avenues, including sildenafil, esomeprazole, metformin, pravastatin, and vascular endothelial growth factor maternal gene therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, A‐V connections may be absent in TOPS . V‐V anastomoses are the least frequent type of anastomoses seen in monochorionic placentas, but they are seen more commonly in TOPS than in uncomplicated monochorionic pregnancies , and it has been suggested that they may have a role in development of TOPS in some instances .…”
Section: Complications In Monochorionic Twinsmentioning
confidence: 99%
“…Although TOPS is a transfusional process (confirmed by the therapeutic success of separating the vascular connections), other factors, including humoral, are at play that mediate the complex clinical phenotype in these cases . It appears that the key feature in TOPS is one of volume imbalance which is in contrast to TAPS where hemoglobin differences are the principle effect of the transfusion .…”
Section: Complications In Monochorionic Twinsmentioning
confidence: 99%
“…Twin-to-twin transfusion syndrome (TTTS) is a serious complication that affects 1 in 40 multiple gestations 1. In monochorionic twin pregnancies, both fetuses share one placenta that possesses vascular anastomoses on the fetal surface that connect the blood circulation of both twins 2. Vascular anastomoses between the two placentae in dichorionic pregnancies, although rare, have been demonstrated 3.…”
Section: Introductionmentioning
confidence: 99%